2014
DOI: 10.1088/1367-2630/16/6/063068
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast magnetization dynamics in Co-based Heusler compounds with tuned chemical ordering

Abstract: We have studied thin film samples of Co 2 FeSi and Co 2 MnSi with different degrees of chemical ordering using the time-resolved magneto-optical Kerr effect to elucidate the influence of defects in the crystal structure on magnetization dynamics. Surprisingly, we find that the presence of defects does not influence the optically induced magnetization dynamics on the ultrashort timescale (some 100 fs). However, we observe a second demagnetization stage with a timescale of tens of picoseconds in Co 2 MnSi for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The spin-flip scattering can be turned off by the half metallic character of the material, e.g., Figure 3(b), resulting in a decoupling. This has been tested in a series of half metals, oxides, and Heusler alloys with high spin-polarization at around the Fermi level, a summary of M€ uller et al, 103 Steil et al [104][105][106] and Mann et al 107 is given in Figure 8(b). While there is an expected correspondence of demagnetization becoming slower at high spin polarizations that would be consistent with a spin scattering scenario, especially for the small band gap Heusler alloys with specific positions of the Fermi level close to a band edge, these effects can also be largely suppressed due to electrons (or holes) excited at higher energies above (below) the gap.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The spin-flip scattering can be turned off by the half metallic character of the material, e.g., Figure 3(b), resulting in a decoupling. This has been tested in a series of half metals, oxides, and Heusler alloys with high spin-polarization at around the Fermi level, a summary of M€ uller et al, 103 Steil et al [104][105][106] and Mann et al 107 is given in Figure 8(b). While there is an expected correspondence of demagnetization becoming slower at high spin polarizations that would be consistent with a spin scattering scenario, especially for the small band gap Heusler alloys with specific positions of the Fermi level close to a band edge, these effects can also be largely suppressed due to electrons (or holes) excited at higher energies above (below) the gap.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…These atomic currents excited coherently with the laser field are still maintained shortly after the pulse and result in an evolution of spin and momentum, decreasing the magnetization. 108,109,110,111,112 .…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Another supercell consisting of 8 MLs of CFA on top of 4 MLs of MgO followed by 4 MLs of silver (Ag) and a 25 Å vacuum along the (001) direction are constructed, as shown in figure 5, with the same in-plane lattice parameter as the previous interface model. The Ag layer, which is often used experimentally as a buffer layer for epitaxial growth of cobalt-based Heusler compounds [50,51], is used here to eliminate the screening charges at the the other CFA surface. Previous theoretical work [11] revealed strong ME effects at the surfaces of FM (Fe, Co, Ni) films: both the magnetization and the MCA can be notably changed by a longitudinal electric field, and it is the spin imbalance of excessive surface charges induced by spindependent screening that gives rise to this ME effect.…”
Section: Magnetoelectric Effect: Electric-field-assisted Magnetizatiomentioning
confidence: 99%
“…4a). It may also be noted that the measured τ M for CFA is similar to that of 3d transition metals [48,49] and very much shorter than that of CrO 2 or Fe 3 O 4 .…”
mentioning
confidence: 71%
“…From a fundamental point of view, it is intriguing to ask, how the band gap in the minority spin channel effects the ultrafast magnetization dynamics of Heusler alloys [46,47]. It has already been reported that some of the half-metals like CrO 2 and Fe 3 O 4 exhibit very slow dynamics, involving time-scales of hundreds of picoseconds, [46,47] while several Co-based Heusler alloys show a much faster demagnetization, similar to the time-scales of the elemental 3d-ferromagnets [48][49][50]. The faster dynamics of these Heuslers has been discussed in Ref.…”
mentioning
confidence: 99%